Adaptation of Audiovisual Contents and Their Delivery Means. - DIALLO, MAMADOU TOURAD; MOUSTAFA, HASSNAA; AFIFI, HOSSAM; MARECHAL, NICOLAS (Communications of the ACM, 2013)
The article discusses adaptation of audiovisual contents and their delivery means in the 21st century. The authors argue that online video services, such as mobile television (TV), Internet Protocol television (IPTV), and WebTV, provide content adaptation techniques under the form of adaptive streaming protocols, noting that these protocols rely mostly on network status, central processing unit (CPU) usage, and screen resolution. Topics include approaches to content adaptation and its application within media types, such as server-based, client-based, and intermediate proxy approaches, several video streaming techniques for delivering audiovisual content, such as via the HTTP computer network protocol, and content adaptation for mobile TV, IPTV, and WebTV services.